Post-conflict development in East Asia - Howe, Brendan M. (Rethinking Asia and international relations, 2014)
This volume critically assesses measurements of success in East Asian post-conflict development from a human-centered perspective. This involves a major re-evaluation of accepted accounts of domestic governance and international relations in East Asia from both a comparative and inter-disciplinary viewpoint.